2021
DOI: 10.1177/14680173211009714
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional dynamics that promote client empowerment in mental health practice: A social work perspective

Abstract: Summary Interprofessional practice has been broadly endorsed as a strategy which supports the delivery of high-quality health services. Few studies have addressed the dynamics inherent to interprofessional mental health practice in an era in which client empowerment is prioritised and valued. Social work perspectives are also underexplored in the studies which have been published on interprofessional health care, despite the increasingly important role of this discipline in community mental health contexts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…This study found that there are diverse perspectives and divergences in empowerment action among MHSPs. This is consistent with the findings of previous studies on the understanding of multidisciplinary dynamics in promoting empowerment in mental health practice (90). This may be related to the fact that empowerment itself is a multifaceted concept (87), as well as to the disciplinary boundaries and cultures of the values of different professions, as revealed by studies of multidisciplinary collaborative empowerment.…”
Section: Discussionsupporting
confidence: 91%
“…This study found that there are diverse perspectives and divergences in empowerment action among MHSPs. This is consistent with the findings of previous studies on the understanding of multidisciplinary dynamics in promoting empowerment in mental health practice (90). This may be related to the fact that empowerment itself is a multifaceted concept (87), as well as to the disciplinary boundaries and cultures of the values of different professions, as revealed by studies of multidisciplinary collaborative empowerment.…”
Section: Discussionsupporting
confidence: 91%
“…Within the hierarchal yet collaborative setting of interprofessional primary health care, researchers have identified particular issues; these issues mirror my experience within my practicum context. At times, interprofessional teams have been shown to result in poor outcomes for the client as space for advocacy, social justice, or client empowerment is not prioritized (Cui et al, 2022). The role of social worker as advocate has been shown to sometime result in conflict within interprofessional teams (Ambrose-Miller & Ashcroft, 2016).…”
Section: Abolitionist Social Workmentioning
confidence: 99%
“…The role of social worker as advocate has been shown to sometime result in conflict within interprofessional teams (Ambrose-Miller & Ashcroft, 2016). Power differentials within decision-making processes may regulate social work perspectives to the bottom of the hierarchy (Ambrose-Miller & Ashcroft, 2016;Cui et al, 2022). Tensions are inherent between the medical model of symptom management and social work's emphasis on empowerment (Cui et al, 2022) and human rights.…”
Section: Abolitionist Social Workmentioning
confidence: 99%
See 1 more Smart Citation